COMPARATIVE ANALYSIS OF THE RABBIT MEAT PRODUCTION IN BALKAN COUNTRIES, MEMBERS OF THE EUROPEAN UNION - Delyana DIMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Data about rabbit meat production are provided from the web site of Food and Agriculture Organization of the United Nations. The mentioned information for the studied three Balkan countries (Bulgaria, Romania and Greece) has been extracted and organized in a created relational database. Different parameter queries have been used for visualization of certain subsets from the indicated database. Subsequently, they have been processed and evaluated. The article presents comparative analysis of the rabbit meat production in these Balkan countries for the period 1984-2018. Hierarchical cluster analysis has also been applied to the considered data. The grouping of the investigated indicator is discussed. The obtained results showed that the rabbit meat production in Romania increased significantly for 1984-1990. The same process was observed in Bulgaria and Greece during 1987-1997 and 1988-1993, respectively. The values of this indicator for Greece and Bulgaria are quite higher in comparison with those ones in Romania for 2006-2018. A decreasing tendency in the rabbit meat production in the listed three countries was established for the last five years of the time interval.